MDM2 antagonists promote CRISPR/Cas9-mediated precise genome editing in sheep primary cells - Yan Li; Di Lian; Jiahao Wang; Yue Zhao; Yao Li; Guoshi Liu; Sen Wu; Shoulong Deng; Xuguang Du; Zhengxing Lian (Elsevier, 2023)
CRISPR-Cas9-mediated genome editing in sheep is of great use in both agricultural and biomedical applications. While targeted gene knockout by CRISPR-Cas9 through non-homologous end joining (NHEJ) has worked efficiently, the knockin efficiency via homology-directed repair (HDR) remains lower, which severely hampers the application of precise genome editing in sheep. Here, in sheep fetal fibroblasts (SFFs), we optimized several key parameters that affect HDR, including homology arm (HA) length and the amount of double-stranded DNA (dsDNA) repair template; we also observed synchronization of SFFs in G2/M phase could increase HDR efficiency. Besides, we identified three potent small molecules, RITA, Nutlin3, and CTX1, inhibitors of p53-MDM2 interaction, that caused activation of the p53 pathway, resulting in distinct G2/M cell-cycle arrest in response to DNA damage and improved CRISPR-Cas9-mediated HDR efficiency by 1.43- to 4.28-fold in SFFs. Furthermore, we demonstrated that genetic knockout of p53 could inhibit HDR in SFFs by suppressing the expression of several key factors involved in the HDR pathway, such as BRCA1 and RAD51. Overall, this study offers an optimized strategy for the usage of dsDNA repair template, more importantly, the application of MDM2 antagonists provides a simple and efficient strategy to promote CRISPR/Cas9-mediated precise genome editing in sheep primary cells.